2014
DOI: 10.1128/jcm.00907-14
|View full text |Cite
|
Sign up to set email alerts
|

Development and Clinical Evaluation of sdaA Loop-Mediated Isothermal Amplification Assay for Detection of Mycobacterium tuberculosis with an Approach To Prevent Carryover Contamination

Abstract: A rapid and sensitive loop-mediated isothermal amplification assay for the sdaA gene of Mycobacterium tuberculosis was developed using a dUTP-uracil-N-glycosylase (dUTP-UNG) strategy to prevent carryover contamination. Evaluation of the assay using clinical specimens (n ‫؍‬ 648) showed high specificity (97.2%) and sensitivity (100%), demonstrating its potential as a diagnostic test for tuberculosis, especially in resource-limited settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Although these studies have revealed generally very good diagnostic performance, there are considerable discrepancies between their results891011121314151617181920212223242526272829303132. In addition, none of the studies could describe precise diagnostic accuracy because of their limited statistical power.…”
mentioning
confidence: 99%
“…Although these studies have revealed generally very good diagnostic performance, there are considerable discrepancies between their results891011121314151617181920212223242526272829303132. In addition, none of the studies could describe precise diagnostic accuracy because of their limited statistical power.…”
mentioning
confidence: 99%
“…In the previous studies (Nimesh et al . 2014; Joon et al . 2015), the 190 bp region of sdaA has been considered as a diagnostic target for TB diagnosis according to PCR and LAMP.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies (Nimesh et al . 2014; Joon et al . 2015), the 190 base pair (bp) region of the L‐serine dehydratase ( sdaA ) gene has been successfully demonstrated as a specific molecular marker for TB diagnosis using PCR‐based assays; thus, the sdaA gene was a candidate target for establishing reliable diagnosis technique for target pathogen detection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LAMP has been successfully implemented in nucleic acid research, and in clinical application as a screening tool [ 26 ]. Several LAMP-based assays have been developed to detect M. tuberculosis infection, targeting gyrB [ 27 ], rrs [ 28 ], rimM [ 29 ], IS6110 [ 30 ], hspX [ 31 ], mpb64 [ 32 ] and sdaA gene [ 33 ].…”
Section: Introductionmentioning
confidence: 99%